Whole-Brain N-Acetylaspartate Level and Cognitive Performance in HIV Infection - Patel, Sohil H.; Inglese, Matilde; Glosser, Guila; Kolson, Dennis L.; Grossman, Robert I.; Gonen, Oded (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: In the brain of HIV-infected patients, proton MR spectroscopic studies are typically used to examine small volumes of tissue with single-voxel methods. Since brain disease is diffuse in patients with HIV, such studies preclude assessment of the true extent of the metabolic burden. To assess this extent, the relationship between global neuronal integrity, reflected by the whole-brain N-acetylaspartate (WBNAA) concentration, was correlated with neuropsychological function and the AIDS dementia complex (ADC) stage score.METHODS: WBNAA levels were compared between 15 HIV-infected patients (seven symptomatic, eight asymptomatic) and 13 age- and sex-matched healthy subjects. The patients’ WBNAA level was correlated with cognitive performance, as measured with a battery of eight tests (NPZ-8), including the ADC stage score and four total-memory, mood, motor, and processing speed subtests.RESULTS: WBNAA levels were significantly different between patients and healthy subjects (mean ± σ, 11.82 ± 1.40 and 12.91 ± 1.03 mmol/L, respectively; P = .032) after we adjusted for age and sex effects. Intermediate negative correlations were found between the WBNAA level, the processing speed subtest score (r = −0.50, P = .03), and the ADC stage score (r = −0.44, P = .05).CONCLUSION: The WBNAA concentration complements brain atrophy data with information about the quality of the remaining neuronal and axonal tissue in patients with HIV infection. In HIV-infected patients, its correlation with processing speed and the ADC score indicates that the latter reflects pathologic deficits, which are extensive throughout the brain.